(untitled) (Baghdad Science Journal, 2004)
World wide web is one of the cornerstone of the internet, and has become a primary source of information, through which one can gain access to different fields of knowledge, as well as commercial fields, entertainment...etc. Internet media is not limited to a country or certain company , and any body can have his own web page. Therefore , not all accessible information are reliable and dependable as scientific references, since some of these information are commercial , other are advertisements, still others are personal views, in addition to the scientific ones. This article deals with the types and patterns of information that are usually obtained from the Internet, and discusses the role of the search engines in reaching the precise and trustable information and how to exclude unreliable information.